Pengenalan Teknologi Virtual Reality dan Augmented Reality Untuk Meningkatkan Pembelajaran Digital di Pondok Pesantren Al Muin Syarif Hidayatullah - Nourma Budiarti, Rizqi Putri; Sulistyani, Endang; Anggraini, Fitria; Marvyna, Hanifah Citra; Manilaturrohmah, Manilaturrohmah (Communautaire: Journal of Community Service, 2022)
Virtual reality and augmented reality technology are notforeign to students, in contrast to students at the Al MuinSyarif Hidayatullah Islamic Boarding School where the use oftechnology and knowledge related to learning innovationswith immersive technology is still common and new forthem. This technology can increase student learningmotivation because the design of the technology used canattract the curiosity of its users, in this case students. Theimplementation method used in this activity is divided intothree stages, namely pre-service activities which include sitesurveys, distribution of pre-test questionnaires andintroductory discussions, service implementation activitiesconsisting of VRAR technology socialization and VRARintroduction and post-service activities which includeevaluation of service activities and distribution of post-testquestionnaires. The results of this community service activityshowed an increase in the level of knowledge of students atthe Al-Muin Islamic boarding school and the usefulness ofthis activity in the introduction of VRAR technology at theAl-Muin Syarif Hidayatullah Islamic boarding school. Theusefulness impact shows an increase in knowledge based onthe results of the post-test as much as 45% com